The Factors Associated with Nomophobia Among Bachelor of Nursing Students at Universitas Muhammadiyah Purwokerto - Khanani Azzahroh; Rakhmat Susilo (Proceedings Series on Health & Medical Sciences, 2024)
Background: Mobile phones have become essential tools for students due to their ability to meet various educational demands and provide access to a wealth of information. Excessive use and dependence on smartphones have also led to a new problem known as nomophobia. Nomophobia is a term derived from the phrase "no mobile phone phobia," which is related to the fear or distress experienced by individuals when they lose or cannot use their smartphones. Objective: This study aims to determine the factors associated with nomophobia among Bachelor of Nursing students at Universitas Muhammadiyah Purwokerto. Method: This quantitative research used a cross-sectional approach. The study sample comprised 92 Bachelor of Nursing students aged 18-24, selected using stratified random sampling. Data analysis included univariate and bivariate analyses using the Chi-Square test. Results: The analysis showed an association between nomophobia and the following factors: learning fatigue with a p-value of 0.029 (less than 0.05), self-esteem with a p-value of 0.012 (less than 0.05), loneliness with a p-value of 0.035 (less than 0.05), and smartphone usage intensity with a p-value of 0.001 (less than 0.05). Conclusion: A correlation exists between learning fatigue, self-esteem, loneliness, and smartphone usage intensity with nomophobia among Bachelor of Nursing students at Universitas Muhammadiyah Purwokerto.